Examining tax revenue losses from the C2C mode of electronic commerce in China - LIU, YITONG (2018)
This paper started with the basic concepts of e-commerce and tax revenue and adopted the methods of econometrics in attempts to prove the existence of the tax loss of C2C e-commerce mode and elaborate the tax loss degree. The issue of tax in C2C e-commerce mode was explored through the conductive process of the impacts of C2C mode on tax revenue in the research, wherein it selected the proportion of C2C scale in the total retail sales of consumer goods as the index measuring the development condition of C2C e-commerce, chose the tax revenue as the index quantifying the tax development, meanwhile selected the total retail sales of consumer goods and the total amount of online retail shopping as the index quantifying the retail industry of real economy and had a conduction effect. In this paper, the influence degree of the online retail shopping of C2C e-commerce on retail price index through establishing was explored and the measurement model for the proportions of retail price index and C2C limit in the total retail sales of consumer goods was analyzed to work out the influence degree of online retail shopping of C2C e-commerce on the tax through the positive correlation between retail price index and tax revenue.